Effect of season, lactation, parity and milk production on milk inflammatory parameters in healthy and mastitis infected Sahiwal cows - INDU PANCHAL; SUMIT MAHAJAN; JINU MANOJ; DEEPTI DHINDSA (Indian Journal of Animal Sciences, 2022)
The present investigation was undertaken to study the effect of different season, stages of lactation, parity and milk production on milk inflammatory parameters in healthy and mastitis infected Sahiwal cows. Three parameters, viz. pH, electrical conductivity (EC) and somatic cell count (SCC) were taken to assess the quality of milk. The study was conducted on 100 selected Sahiwal cows maintained at livestock farm at National Dairy Research Institute, Karnal, Haryana. Significant higher values of pH, EC and SCC were found in milk samples during rainy season, followed by winter and summer. Effect of parity, lactation and milk production on inflammatory parameters was non-significant. The pH, EC and SCC also differed significantly in healthy, subclinical and clinical stages of mastitis. A significant positive coefficient of correlation was observed between SCC and EC (r=0.679) whereas moderate (r=0.526) but significant positive correlation was found in pH and EC. In view of above results, it can be deduced that the elevated value of pH, EC and SCC indicates inflammation into the udder of the animals which leads to reduced quality of milk. Hence it is imperative that pH, EC and SCC need to be considered along with effective management strategies.